CENTRAL ASIAN GEODYNAMIC REGIMES WEST AND EAST 102–104° GEODIVIDER - Yu. G. Gatinsky; T. V. Prokhorova; D. V. Rundquist (Геодинамика и тектонофизика)
Ample geologic and geophysical data provide the basis for distinguishing the 102–104° E geodivider in the North, Central and South Asia. The geodivider’s central part is confirmed by the data on seismicity, seismically active faults and the modern crust block structure. These data and historical and instrumentally identified earthquake epicenters were used for a more correct definition of the block boundaries and interblock zones in the central part of the geodivider and in its wings. Seismic energy is considerably increased (to 1011–1016 J) in the eastern part of the geodivider’s western wing, and rarely increased directly in the geodivider itself. Near the geodivider, a seismic energy increase is detected east of it only at the western border of the South-Eastern China Block. The authors analyzed deep seismic sections and constructed energy dissipation graphs along transects crossing the geodivider and its western wing. The analysis and the graphs show the predomination of left-lateral NW-striking slips in the north, thrusts to the east and southeast in the center, and right-lateral NE-striking slips in the south. The total seismic energy increases constantly to the west. In the central and northern segments of the geodivider’s central part and west of it, horizontal blocks displacements cause a direct influence on seismicity level increasing and changes in geodynamic regimes within the investigated territory of Central Asia. Changes in the horizontal displacement vector are accompanied by the change of tectonic strain regimes. Increased heat flow values to the east from the geodivider within the East Asian transit zone are probably related to the change of the geodynamic regimes in the same direction under the influence of the submerged Pacific slab. The data obtained by the Chinese and Russian researchers confirm delamination (stratification) processes in the Southeast Tibet crust during its interaction with the colder and thicker lithosphere of Southeast China, and displacement of its upper layers to the southeast and south, as we supposed in our earlier publications.